BITUMEN OBTAINED FROM PETROLEUM TAR (Web of Technology: Multidimensional Research Journal, 2025)
The production of bitumen from petroleum tar is a significant aspect of the petroleum industry, playing a crucial role in road construction, waterproofing, and various industrial applications. The process involves refining heavy residues from crude oil distillation, followed by oxidation, polymer modification, or emulsification, depending on the intended use. This study explores the chemical and physical properties of petroleum tar-based bitumen, its production methods, and the impact of technological advancements on its quality and efficiency. A particular focus is placed on Uzbekistan's potential in the bitumen industry, considering its oil refining capacities and growing demand for road construction materials. The research highlights the advantages and challenges associated with producing bitumen from petroleum tar, including environmental considerations, economic feasibility, and material performance. The study also discusses various methodologies employed to enhance bitumen properties, ensuring improved durability and resistance to environmental conditions.